Mechanical normal dispersive N LHS shock waves of microfluidics in shallow model - Sevgin, Fatih; Körpınar, Talat (World Scientific Publ Co Pte Ltd, 2024)
In this paper, we obtain normal dispersive N LHS shock waves for phi(J(1)), phi(J(2)), phi(J(3)) dam-break intensity by the nonlinear heat system. Then, we obtain super-fluid normal dispersive N LHS shock waves for phi(J(1)), phi(J(2)), phi(J(3)) dam-break microfluidics. Finally, we illustrate thermonormal N LHS pressure of phi(J(1)), phi(J(2)), phi(J(3)) wave energy with normal dam-break in shallow water.
Keywords: Shallow wave energy; optical shock waves; turbulence model; dam break flows